Analysis Of The Added Value Of Goat Manure As Organic Fertilizer In Carangwulung Village, Wonosalam District - Rizkiyah, Salsabila Putri Ainur; Avivah, Elmira Dhiva; Armana, Andru; Rahman, Toriq Aulia; Rozci, Fatchur (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
The high population of goats in Carangwulung Village causes high amounts of animal waste to be produced on the goat farm, of course, this must be managed well so that it does not hurt the environment. The chairman of LMDH "Rimba Jaya Makmur" manages goat manure to be used as organic fertilizer which will later be commercialized and used to fertilize plants owned by LMDH. The main aim of this research is to determine the added value of goat manure which produces organic goat manure fertilizer. The location for this research was deliberately chosen in Carangwulung Village, Wonosalam District, specifically in the LMDH "Rimba Jaya Makmur" for research because the head of the LMDH "Rimba Jaya Makmur" manages goat dung. The method used is the Hayami method. The results of this research are that in managing the production of goat manure fertilizer, it has an input of 2000 kg and gets an output of 1,999 kg, thus providing added value, namely Rp. 939/kg, where the added value is > 50%, so it is classified as high and the business is worth continuing.